If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13xy + 9y + -9xy + 18y = 0 Reorder the terms: -13xy + -9xy + 9y + 18y = 0 Combine like terms: -13xy + -9xy = -22xy -22xy + 9y + 18y = 0 Combine like terms: 9y + 18y = 27y -22xy + 27y = 0 Solving -22xy + 27y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27y' to each side of the equation. -22xy + 27y + -27y = 0 + -27y Combine like terms: 27y + -27y = 0 -22xy + 0 = 0 + -27y -22xy = 0 + -27y Remove the zero: -22xy = -27y Divide each side by '-22y'. x = 1.227272727 Simplifying x = 1.227272727
| -xy+-9xy= | | 25ab-37ab= | | 3[x-2]=2x+6 | | 110-90= | | 50+60= | | 12a-14a=3 | | -4n-8/17=23 | | a+c/2x=b | | x^2+2x=37 | | 2[x+3]=x+10 | | 6(3.14)=3.14x | | 2x+6=x+10 | | 2/x=5/x-6 | | 211c=105 | | q+(-10)=2 | | (y/4)=-7 | | p-8/(1/2)=-3 | | 100g=20 | | 72n=9 | | (2x+3)+(-3x+1)= | | -8/1/2=-3 | | -6x+3=-20 | | 10x-6=7-12 | | x+5.1+9.4=18.2 | | x+5.1+9.5=18.2 | | x-85=-5+-7 | | 24a-12ab= | | X^2+9x-234=0 | | 3x-4y-16=o | | -2/3*-3+5 | | (-2/3x-3)+5 | | X/5=49 |